A Comprehensive Systematic Review of Treatment Strategies for Keloid and Hypertrophic Scar - Elvantie; Virgina Maurila Palakkang; Petra Damiana Anindita (The International Journal of Medical Science and Health Research, 2026)
Introduction: Keloid and hypertrophic scars represent a significant clinical challenge due to their complex pathogenesis, propensity for recurrence, and psychosocial impact on patients. Despite numerous available interventions, there is no universally accepted gold-standard treatment, and evidence on comparative efficacy and safety remains fragmented. Methods: A systematic evidence synthesis was conducted based on a comprehensive screening of 80 studies, including randomized controlled trials, systematic reviews, and meta-analyses. Studies were selected based on predefined criteria including clinically diagnosed scars, therapeutic interventions, human studies, and quantitative outcome reporting. Data were extracted on treatment strategies, scar characteristics, patient demographics, effectiveness, safety, and study design. Results: Combination therapies consistently outperformed monotherapies. Triamcinolone acetonide (TAC) combined with 5-fluorouracil (5-FU) showed superior efficacy (77.2–93.3% response) and lower recurrence compared to TAC alone (Liu et al., 2020; Khalid et al., 2019). TAC with botulinum toxin A also ranked highly (SUCRA 82.2%) (Yang et al., 2021). Verapamil demonstrated a better safety profile but slower onset of action. Laser therapies, especially fractional CO₂ with 5-FU, showed significant scar improvement (Foppiani et al., 2024). Surgical excision with adjuvant high-dose-rate brachytherapy yielded the lowest recurrence (3.1%) (van Leeuwen et al., 2014). Discussion: The synthesis highlights the importance of multimodal, context-specific treatment strategies. Combination regimens address multiple pathological pathways, enhancing outcomes while mitigating adverse effects. Discrepancies in monotherapy efficacy are attributed to variations in protocols, concentrations, and scar characteristics. Conclusion: Combination therapy, particularly TAC+5-FU, represents the most effective and balanced approach for most keloid and hypertrophic scar cases. Treatment should be individualized based on scar type, location, size, patient skin type, and tolerance to side effects. Future research should focus on standardized protocols, long-term follow-up, and novel targeted therapies.